Answer:
c(10) = 4
Step-by-step explanation:
3+p=8
-p -p
3=8-p
-8 -8
-5=-p
swap signs
5=p
Answer:
Zero Slope
Step-by-step explanation:
rise over run or y2 - y1 / x2 - x1
6-6/5-2 = 0/3
x =
or x = - ![\frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D)
consider the factors of the product 6 × - 4 = - 24 which sum to the coefficient of the x- term ( + 5)
the factors are + 8 and - 3 ( split the middle term using these factors
6x² - 3x + 8x - 4 = 0 ( factor by grouping )
3x(2x - 1) + 4(2x - 1 ) ( take out common factor of (2x - 1) )
= (2x - 1)(3x + 4) = 0
equate each factor to zero and solve for x
2x - 1 = 0 ⇒ x = ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
3x + 4 = 0 ⇒ x = - ![\frac{4}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D)
Answer:
3/-8
Step-by-step explanation:
Slope= y2-y2/x2-x1
substitute in: 8-5/-7-1= 3/-8